2008
DOI: 10.1177/088840640803100206
|View full text |Cite
|
Sign up to set email alerts
|

Middle School Special Education Teachers' Instructional Practices for Solving Mathematical Word Problems: An Exploratory Study

Abstract: A random sample of middle school special education teachers from various classroom settings completed a survey asking them about what instructional practices and materials they used to teach students with disabilities how to solve word problems, how much time they allocated to problem solving instruction, and what type of problems they gave their students to solve. Overall, regardless of setting, the teachers focused primarily on instructional practices that teach students how to solve word problems (e.g., vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Problem solving has become a skill that is infused in all areas of mathematics (NCTM, 2000). Yet researchers have suggested that middle school special educators spend only 1 hour per week on teaching problem solving (van Garderen, 2008). Using explicit instruction (Hudson, Miller, & Butler, 2006) to teach cognitive strategies may provide students with EF deficits the support needed to make the connections between procedural learning (processes) and declarative learning (rote factual knowledge), which may result in conceptual knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…Problem solving has become a skill that is infused in all areas of mathematics (NCTM, 2000). Yet researchers have suggested that middle school special educators spend only 1 hour per week on teaching problem solving (van Garderen, 2008). Using explicit instruction (Hudson, Miller, & Butler, 2006) to teach cognitive strategies may provide students with EF deficits the support needed to make the connections between procedural learning (processes) and declarative learning (rote factual knowledge), which may result in conceptual knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have examined special education teachers’ instructional use of VRs. Overall, teachers indicate a preference to use VRs, but they may not be used as frequently or as consistently as desired (van Garderen, 2008; Gagnon & Maccini, 2007). Despite this research, no study to date has specifically examined special education teachers’ knowledge of VRs for solving mathematical problems and what they emphasize and teach about VRs as a strategy to solve problems in their instruction for SWDs.…”
Section: Teacher Knowledge and Instructional Application About Vrsmentioning
confidence: 99%
“…Legislation such as the NCLB 2001 and the Individuals with Disabilities Act (IDEA, 2004) call for students with disabilities to have access to the same general education curriculum as their nondisabled peers (van Garderen, 2008). In addition, IDEA requires that all students, except those participating in alternate state assessments, participate in district and state assessments (Maccini & Gagnon, 2006).…”
Section: Theoretical Framework Of the Baipmentioning
confidence: 99%